2000
DOI: 10.1046/j.1365-2796.2000.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Signs of neuropathy in the lower legs and feet of patients with acute intermittent porphyria

Abstract: Abstract. Wikberg A, Andersson C, Lithner F (University of Umea Ê, Umea Ê; Primary Health Care Centre, Arjeplog; and University Hospital, Umea Ê, Sweden). Signs of neuropathy in the lower legs and feet of patients with acute intermittent porphyria. J Intern Med 2000; 248: 27±32.Objective. To assess signs of distal neuropathy in patients with acute intermittent porphyria (AIP). Design. A population-based study. Subjects. All patients with DNA-verified AIP $ 18 years of age in the four most northerly counties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…[1] Reports have documented gradual improvement of muscle strength over months [4] to years, but up to 50% of patients may have residual weakness [5] and 4% remain quadriparetic. [6] However, fairly rapid improvement on haem arginate, similar to that which our patient experienced, has been observed in several cases. [7,8] The dramatic clinical recovery observed in our patient's proximal muscles over a few days argues for a substantial contribution from neural dysfunction rather than neural degeneration.…”
Section: Discussionsupporting
confidence: 86%
“…[1] Reports have documented gradual improvement of muscle strength over months [4] to years, but up to 50% of patients may have residual weakness [5] and 4% remain quadriparetic. [6] However, fairly rapid improvement on haem arginate, similar to that which our patient experienced, has been observed in several cases. [7,8] The dramatic clinical recovery observed in our patient's proximal muscles over a few days argues for a substantial contribution from neural dysfunction rather than neural degeneration.…”
Section: Discussionsupporting
confidence: 86%
“…Slight peripheral neuropathy with reduced conduction velocity of the motor and sensory fibres has been reported years after recovery from attacks and even by AIP patients who never had attacks [20,21]. Signs of distal chronic symmetrical sensory and motor neuropathy have been reported by patients with manifested AIP [6]. Behavioural, structural and electrophysiological data in PBGD deficient mice are evidence of predominantly axonal motor neuropathy, most likely caused by haeme deficiency and consequent dysfunction of haeme proteins in the nerve cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of these symptoms is 45–70% whereas the incidence of muscle weakness and paresis is 40–60% as reported in five large series from 1957 to 1976 [3]. Grave paresis seems to be uncommon nowadays, probably because of awareness of and avoidance of precipitating factors and thanks to the use of specific haeme therapy [6–8]. The cause of the neurological dysfunction in AIP is not known.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, the degree of axonal damage probably pre dicts the ultimate prognosis and recovery often takes many months with some patients remaining permanently quadriparetic. [4,13] In the SA study that reported on clinical features recorded during 112 acute porphyric attacks, three patients with quadriparesis improved with rehabilitation and eventually regained the ability to walk. In the same study, several other patients with pre-existing neuropathy deteriorated markedly at the onset of a new attack, but the weakness resolved rapidly after haemin administration.…”
Section: Discussionmentioning
confidence: 99%